Development and assessment of a hydrogen car operated by a vertical axis wind turbine - Oruc, Onur; Dincer, Ibrahim (TAYLOR & FRANCIS INC, 2023)
In this study, an electrolysis unit which is driven by a vertical wind turbine in a fuel cell passenger car is investigated for hydrogen production thermodynamically through exergy and energy approaches. The proposed system essentially consists of a vertical axis wind turbine, an electrolysis unit, and a fuel cell unit, as well as the auxiliary units. The electrical energy generated by the wind turbine is used to operate the electrolyzer for hydrogen generation. The hydrogen generated is then sent to fuel cell for driving the car and/or hydrogen tank for storage. Both energy and exergy efficiencies of the electrolysis unit are found to be approximately 63% at 975 mA/cm(2) current density. Additionally, the energy and exergy efficiencies of the proposed system are calculated as 39% and 56%, respectively. Furthermore, hydrogen production amount from the electrolyzer is calculated using two different test-driving procedures, which are accepted worldwide. At the end of driving cycle, the amount of hydrogen produced per cell in the WLTP (Worldwide Harmonized Light Vehicles Test Procedure) driving cycle is calculated as 17.06 mol and in the FTP -75 (Federal Test Procedure) driving cycle is calculated as 6.88 mol. The amounts of oxygen are found as 8.53 mol for the WLTP driving cycle and 3.44 mol for the FTP-75 driving cycle, respectively.
Keywords: Hydrogen; electrolyzer; energy; exergy; efficiency; fuel cell; wind turbine; car; FUEL-CELL; WATER; Energy & Fuels; Engineering; Environmental Sciences & Ecology